Analisis Keanekaragaman dan Kelimpahan Plankton di Sungai Way Awi dan Hubungannya dengan Kualitas Air - Tina Pertiwi; Tugiyono Tugiyono; Gregorius Nugroho Susanto (Universitas PGRI Palembang, 2024)
Plankton serves as a bioindicator that can be used as a marker for water quality related to water saprobity index. Way Awi River is a river flowing from the Susunan Baru area, passing through the Tandjungkarang region, and reaching the Garuntang area. Liquid waste from households is often directly discharged into the river, without passing through a containment system such as a septic tank, resulting in river pollution. To understand this relationship, this research was conducted to determine the biological condition of the Way Awi River based on plankton community structure, including abundance index, diversity index, evenness index, and dominance index, as well as its correlation with water quality using Pearson correlation test. The research was conducted in the Way Awi River with sampling taken at five different stations from October to December 2023. Water samples were analyzed using physical parameters including water temperature and turbidity, while chemical parameters observed were pH, DO, BOD, and COD. Based on the analysis of plankton community structure, it was found that the water of Way Awi River is in a moderately polluted condition.